2004
DOI: 10.1063/1.1836865
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting carbon nanotubes

Abstract: Current efforts of guided growth of carbon nanotubes alone cannot make large-scale and directed assembly of them. The nanopelleting concept overcomes this limitation by embedding carbon nanotubes in microscale pellets that can be transplanted readily. This technique includes vertical growth of carbon nanotubes, pellet casting, planarization, pellet separation, and transplantation. A specific manufacturing process is developed and tested with favorable results. This technology will enable directed assembly of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…6 is 1.48 N/m. Taking the CNT diameter to be around 10 nm and its young modulus around 1.25 TPa [7], the effective Hooke's constant at midpoint loading should be around N/m. So, the apparently large slope of 1.48 N/m is due to the maximum stress afforded by the welded CNT contacts on both ends.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…6 is 1.48 N/m. Taking the CNT diameter to be around 10 nm and its young modulus around 1.25 TPa [7], the effective Hooke's constant at midpoint loading should be around N/m. So, the apparently large slope of 1.48 N/m is due to the maximum stress afforded by the welded CNT contacts on both ends.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…However, the precise alignment and stable assembly of such nanostructures into useful individual nanoneedles are still challenging [25]. Reported methods for the assembly of the nanostructures into needle-like structures include direct attachment of nanotubes by using a manipulator [27, 28, 30, 52-55], catalyst-patterning and direct growth of nanotubes by chemical vapor deposition [56-58], alignment and assembly using dielectrophoresis or magnetic fields [25, 59-66], and transplanting of single nanotubes encapsulated in polymer blocks [67, 68]. However, these methods do not reproducibly produce nanoneedles in large quantity or produce high-aspect ratio “water-stable” nanoneedles (that can survive the meniscus forces involved in the intracellular delivery operation) [25, 28, 54].…”
Section: Fabrication Of Nanoneedles For Intracellular Deliverymentioning
confidence: 99%
“…This assembly transforms the scale of tools necessary for CNT assembly from nano-scale to micro-scale, which enables automated, parallel or even manual assembly of individual CNTs to MEMS in a deterministic and reproducible way. Previously, authors reported a bundle of CNTs could be transplanted from where they were grown to where they could function [4]. This paper presents that a single strand CNT can be transplanted to make a CNT-tipped AFM probes which includes detailed design and fabrication process of integrating individual CNTs into MEMS devices and quantitative characterization of physicochemical interactions of the individual CNTs with encapsulating polymers and etchants during the transplanting process.…”
Section: Introductionmentioning
confidence: 98%